Empowering cities and citizens within emerging models of multilevel governance - i Carmona, Ricard Gomà (Ciência & Trópico, 2019)
The article will be dealing with the empowerment of local institutions within a complex context of multilevel governance. The strengthening of cities will lead us to consider a new transformative municipalism. The transition from classic government to relational forms of governance paves the way to consider both emerging multilevel networks and models of citizen involvement at local level. The case of Barcelona today will be shown as an example of boths trends: initiatives of community engagement in urban policymaking, and local-global action at European and international level. KEYWORDS: Networks. Governance. Empowerment. Multilevel.